Away laughing on a fast camel : even more confessions of Georgia Nicolson - Rennison, Louise (New York : HarperTempest, 2004)
The saga of teenager Georgia Nicolson continues in diary entries about her life after her boyfriend goes off to Kiwi-agogoland, leaving her to make do without him.
800
Accelerated Reader AR
Keywords: Interpersonal relations -- Fiction; Dating (Social customs) -- Fiction; Diaries -- Fiction; Humorous stories; England -- Fiction